Does Cataract Surgery Improve the Progression of Age-Related Macular Degeneration? A Meta-Analysis - Yuanyuan Liu; Qinhua Cai (Journal of Ophthalmology)
Purpose. Cataract and age-related macular degeneration (AMD) are the common causes of blindness in the elderly. Although cataract surgery is the most effective treatment for cataract, some clinicians suspect that such interventions may accelerate the progression of AMD. Therefore, we carried out this meta-analysis to focus on demonstrating the effectiveness and safety of cataract surgery in eyes with AMD. Methods. We performed a systematic literature search in the PubMed, EMBASE, and Cochrane Library databases, and the electronic databases were last searched in January 2019. We planned to include cohort trials of eyes affected by both cataract and AMD in which cataract surgery would be compared to no surgery. Two reviewers independently evaluated the search results against the inclusion and exclusion criteria. 8 trials were included for this meta-analysis. Results. We used the Stata/12.0 to integrate the data that was extracted from the articles. Eight cohort trials with data from different study populations were included. In random effects model, the relative risk (RR) for the progression of AMD is 1.194 (95% CI 0.897–1.591). As for those grouped according to the follow-up year, the RR for longer than five years was 1.372 (95% CI 1.062–1.772). Conclusion. We could draw out such a conclusion that there is still a positive correlation between cataract surgery and the progression of AMD, especially for the Asians. However, based on the current results, it is not possible to draw conclusions from existing studies on the impact of cataract surgery on early AMD development.